Yeast functional genomics and cell biology: no longer in the dark - Friesen, Helena (BioMed Central, 2003)
A report on the Cold Spring Harbor Laboratory meeting 'Yeast Cell Biology', Cold Spring Harbor, USA, 12-17 August 2003.